Diferentes fontes de nitrogênio em condições de aplicações antes e pós-precipitação de chuva no milho - Tomadon, Renan (2019)
In order to increase efficiency of N (nitrogen) use for a better production in maize (Zea mays), new practices of fertilizer application have been sought. Nitrogen is one of the essential nutrients for maize, for this purpose it is commonly used for increased production. The experiment was conducted at the experimental farm of the Universidade Tecnológica Federal do Paraná - Campus Dois Vizinhos. The hybrid used was Pioneer® 30 f 53, established at a spacing of 0.45 m between row and sowing density of 70,000 ha-1 plants. The experiment was conducted in a factorial scheme (2 x 6 + 1). The factor A determined by the use of six different sources of N and the factor B the moment of application and the control, without N. The sources of N were: urea with urease inhibitor, ammonium sulfate A, ammonium sulfate 2, urea, protected urea and ammonium nitrate. Each of the treatments with N received 150 kg ha-1 from the nitrogen source, being applied before the precipitation of rain and after precipitation of rain, in only one application in the V6 stage. According to the data obtained, we can observe that the source of N used presented different effects for the variables chlorophyll, yield and grains per row, being not significant for the other variables. In the present study, only the control presented lower chlorophyll content in comparison to the other treatments. It can also be observed that even supplying the nutritional requirements of the crop, the different sources of N were able to promote different responses as to grain yield. Considering all these results, urea and ammonium sulfate presented better performance than the other treatments.